An exploratory study of educational participation issues confronting active duty Air Force personnel assigned to McConnell Air Force Base - Harrison, Terry L. (Kansas State University, 2012)
Serving in the military today is a very specialized and intense experience, with the use of technology requiring dedicated training and education. The military provides much of this specialized training, but also recognizes the value of higher education for its personnel. Our military personnel are supporting our country daily and their increased time away from their home station diminishes time for their personal pursuits which, for many of them, is off-duty education. This exploratory study sought to understand the perceived barriers and goals influencing participation in postsecondary education by active duty Air Force personnel, in particular those that have served in austere, remote locations. This study used a modified version of Finks’ survey design to develop a questionnaire. The survey was administered to airmen, non-commissioned officers, and officers who were stationed at McConnell Air Force Base. Data examining motivational factors and barriers to participation in postsecondary education were analyzed using descriptive and nonparametric statistical tests. Comparative analyses were conducted based on data from the demographic portion of the survey. Goals for postsecondary participation included preparing for when they leave the military, securing professional advancement, giving them higher status in their jobs, and increasing competence in their jobs. Time was identified as a barrier, including not having time to study, taking time away from family or giving up leisure time. Some respondents indicated that the available courses did not seem interesting or that they did not enjoy studying. Other commonly reported barriers included not being able to attend class regularly or because the course was offered at an inconvenient time or location. A number of respondents also indicated that courses not being offered at remote locations was a barrier to their participation in postsecondary education. Although this was an exploratory study, the results can inform future empirical research as well as contribute to the literature focusing on personnel management. The findings from this study can be used as a first step that will allow the Air Force, postsecondary institutions and other stakeholders to enhance educational opportunities for this group and inform organizational effectiveness.
Keywords: Adult education; Postsecondary education; Participation; Barriers; U.S. Air Force; Active duty military; Adult Education (0516); Higher Education (0745)